(untitled) - Huxley, Aldous (London, 1994)
Two classic complete books -- The Doors of Perception (originally published in 1954) and Heaven and Hell (originally published in 1956) -- in which Aldous Huxley, author of the bestselling Brave New World, explores, as only he can, the mind's remote frontiers and the unmapped areas of human consciousness. These two astounding essays are among the most profound studies of the effects of mind-expanding drugs written in the twentieth century. These two books became essential for the counterculture during the 1960s and influenced a generation's perception of life.
Keywords: Peyote,Mescaline,Visions